Epistemic Markers in NS and NNS Academic Writing - Vandenhoek, Tim (Journal of Academic Writing, 2018)
The use of epistemic markers – words and phrases employed to show differing degrees of certainty and hesitation – is an important element of academic writing. Previous research has suggested that this is an area in which non-native speakers (NNS) struggle. Studies have indicated that NNS are prone to making overly strong statements and exhibit less range and sophistication in the devices that they do employ than native speakers (NS). However, there have as yet been few studies examining the use of such language by advanced NNS students in university academic writing. This corpus-based study examines the ways in which NS and advanced NNS students use epistemic markers in university academic writing. Two corpora totalling 31 659 words were formed from the discussion and conclusion sections of a written university assignment and analyzed for use of epistemic markers. The results indicate that though both groups employ the language at comparable rates and display similar levels of commitment in their writing, these NNS writers display some features of epistemic marker use found to be generally characteristic of other NNS writers.